Auditor Reporting and Regulatory Sanctions in the Broker‐Dealer Industry: From Self‐Regulation to PCAOB Oversight - Schnader, Anne Leah; Bedard, Jean C.; Cannon, Nathan H. (Contemporary Accounting Research, 2019)
ABSTRACT The financial security of the investing public relies on high‐quality service by broker‐dealers (BDs), investors' gateway to the financial markets. The SEC has long required auditors to attest to BDs' internal controls and compliance with regulations (including those privately owned). Following the unraveling of the Madoff Ponzi scheme in 2008, the SEC required auditors of all BDs to register with the PCAOB, and Congressional initiatives signaled imminent transition from private (AICPA) to public (PCAOB) oversight. We investigate whether audit quality increased following this transition by measuring whether auditors report material internal control and compliance problems for BD clients where a deficiency presumably existed (i.e., BDs sanctioned by the Financial Industry Regulatory Authority for transgressions against stakeholders). Overall, we do not find increased reporting quality following the regulatory shift but do observe variation by auditor group and BD ownership. While reporting quality for global network firms (GNFs) increases slightly, lower reporting quality observed prior to the regulatory shift for specialist audit firms (having large BD portfolios but small overall size) is exacerbated afterward. This finding complements results of PCAOB inspections and other research identifying audit quality problems among small, industry‐specialized firms in non‐public client settings. Focusing on deficiencies likely more difficult to detect, we find lower reporting quality for private relative to publicly affiliated BDs prior to PCAOB oversight, and lower reporting quality for very small audit firms relative to GNFs following the regulatory shift.